(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The relationship between tellurocracy and thalassocracy is built on the basis of opposition. This is explained not by the fact that the relationship between them acquires a social character, but also by the fact that their social relations are oriented to "gaining power". The conflict between them develops at different points of the Earth in different degrees and in different forms according to the times. However, for geopolitical dualism, the space is only one - Earth or world geopolitical space. The article analyzes the characteristics of these two geopolitical players and their contemporary trends.